A novel decoupled model for water and heat coupling in frozen soil and numerical analysis - Peipei Chen; Zhi Shang; Ruisong Zhu; Qingfeng Yin; Lei Dong; Shan Feng (Scientific Reports)
Abstract A theoretical model for coupled water-heat processes in frozen soil, considering phase change effects, is developed based on energy and mass conservation principles and the soil freezing curve. Through mathematical derivation, a novel decoupled control equations are obtained to facilitate numerical implementation. The differential equation module of the COMSOL platform is redeveloped, and the decoupled water-heat coupling theory of frozen soil is embedded to realize numerical modeling. Based on in-situ monitoring data from cold region subgrade, the reliability and accuracy of numerical calculations were validated. Subsequently, the subgrade in a specific region of Northwestern China was chosen as the research subject, and an analysis was conducted on its water-heat migration response characteristics under surface conditions. The research results are expected to provide some technical support for engineering practice.